Detection of the Effect of Climate Change on the Mechanism of Heat Islands in Tehran Province - Niloofar Mohammadi; Zahra Hejazizadeh; Parviz Zeaiean Firouzabadi; Alireza Karbalaee (Nīvār)
Global climate has had significant changes and consequences during the last century with the development of urbanization. So the combination of urbanization development and climate change has caused cities globally to become hotter and more dangerous places. Iran is a country that has become extremely vulnerable to the effects of climate change, this vulnerability will probably become more severe in the future in industrial metropolises, including Tehran. Therefore, the aim of this research was to reveal the effect of climate change on the mechanism of thermal islands in Tehran province. In the first step, the data of the common daily period of the synoptic stations (Mehrabad, Shemiran, Abali, Firouzkoh, Chitgar, and Geophysics) of Tehran province in the period (1996-2020) were obtained from the Meteorological Organization. In this research, the Mann-Kendall test was used to examine the trend of temperature and precipitation, and the LARS-WG7 model was used to predict temperature and precipitation, in order to identify the changes in the temperature of the earth's surface in the time period (2000-2023) from the data of satellite images. Modis was used in Google Earth Engine. Examining the trend of the temperature time series with Mann-Kendall test of all stations showed an increasing trend, in the exam of the rainfall time series of the stations (Abali, Shemiran and Mehrabad) in the months of October and November, it was accompanied by sudden changes and jumps, which due to the increase in extreme events It is justifiable. in the HadGEM3 model according to the SSP5 scenario; The temperature forecast of Mehrabad station during the period (2060 to 2021) has shown the highest temperature compared to the base period in July with a 5% increase; And the most rainy period is projected to early autumn and winter in the period (2021-2060). According to the analysis with MODIS satellite images, the night temperature changes in the northern areas of Tehran were an increasing trend. Examining the changes in the average night temperature, except for the northern and northeastern areas of Tehran, other areas showed an increase in temperature due to high density and expansion of urbanization. So, this increase in average temperature is shown more in the west of Tehran than in the central and eastern areas of Tehran. that the heat island effect is more in these areas. Tehran has faced climate change caused by global warming. Considering Tehran's new climate, it is necessary to develop a national climate change action plan to reduce emissions, pay attention to the future urban temperature, and adapt to global warming.